Up-to-Date Materials of Gas Ducts and Smoke Stacks - V. D. Sizov; V. V. Pitirimov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers existing systems of smoke removal from heat-generating plants of various heat power. Advantages and disadvantages of every system are specified in the paper. The paper analyzes properties of fiberglass smoke stacks.